Removal of fluoride and ammoniacal nitrogen from fertiliser wastewater industry using acetylene production sludge (APS) / Nur Ain Mohd Zainuddin ... [et al.] - Mohd Zainuddin, Nur Ain; Md Rodzay, Rohaiyati; Ismail, Kamariah Noor; Puasa, Siti Wahidah (Universiti Teknologi MARA, 2022)
Wastewater from the fertiliser industry has caused a major problem to the inland water due to the high contaminant of fluoride and ammoniacal nitrogen (AN). Acetylene production sludge (APS) was chosen in this study due to its efficiency. Its properties can aid the wastewater treatment process and it is also environmentally friendly. The characteristics of APS were anaysed by using X-ray diffraction (XRD) and X-ray fluorescent (XRF). This investigation was not only for fluoride and AN removal, but also on chemical oxygen demand (COD) of the wastewater. Jar test was conducted, on the percentage removal of fluoride and AN by varying the parameter such as pH and APS dosage. Fluoride and AN were found to be reduced at an optimum APS dosage of 2.0 g with a pH of 10.18. Meanwhile COD was reduced at an optimum APS dosage of 2.5 g with a pH of 11.38. The maximum percentage removal of fluoride, AN and COD were 15.02%, 51.84%, and 6.64% respectively. The APS performance was then validated by multilinear regression using Excel Data Analysis ToolPak based on the experimental data obtained. The study shows that APS is a waste material that has a potential to be repurposed for treating fluoride and AN contaminated wastewater.